Kurz erklärt: Fahrrad. - (:unkn) unknown (My University, 2017)
Die Broschüre "Kurz erklärt: Fahrrad" kann unter https://www.bmvi.de/SharedDocs/DE/Publikationen/K/ broschuere-kurz-erklaert-fahrrad.html heruntergeladen werden.
Keywords: Fahrradverkehr; Individualverkehr; Fahrrad; Fahrradnutzung; Fahrradbenutzung; Radverkehrssicherheit